Digital Democracy and Student Contribution to Fight Hoaxes in Pattimura University Campus Environment - Welmince Turwewy; Fricean Tutuarima; Titus Gaite (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The practice of digital democracy is one of the phenomena that occurs as a result of digital transformation. Digital democracy opens up a flexible space for people in democracy, but besides that people are also faced with a flood of information that tends to contain hoaxes. This study aims to see the contribution of Pattimura University students as part of Indonesian citizens and also scholars in fighting hoaxes in the campus environment. This research uses qualitative research with a descriptive analysis approach. Data were obtained through observation and interviews. The results showed that Pattimura University students see digital democracy as an opportunity for the advancement of democracy and increase student participation and development in democracy, and hoaxes are said to be the main threat to democracy in the digital space, and the key to fighting hoaxes is digital literacy, and the importance of implementing the values of politeness, honesty, tolerance, kinship, unity and unity.